Contextual and Contested: Reassessing Europeanization in the Case of Turkey - Kaliber, Alper (Sage Publications Ltd, 2013)
This article introduces a novel conceptual/analytical framework to Europeanization studies. Its main aims are twofold: first, it problematizes the mainstream usage of the term Europeanization, and the notion of change that it has embraced, and second, it develops a fuller account of the impact of European integration on societies. An analytical distinction is drawn between EU-ization as a formal process of alignment with the EU's body of law and institutions, and Europeanization as a wider sociopolitical and normative context. The impact of Europeanization in a given society is heavily conditioned by the extent and the ways in which Europe is used as a context by domestic actors. To substantiate its arguments, the article focuses on the Turkish case, where Europeanization as a normative-political context has extensively been implicated in its modernization and nation-building processes as well as in recent domestic debates concerning the country's identity and future orientation.
Keywords: Eu-İzation; Europeanization; Modernization; Neoinstitutionalism; Turkey; Identity; Europe